LKJS periodinės spaudos leidimas buržuazijos valdymo metais Lietuvoje. Miestų, rajonų ir parajonių komitetų periodika. (1920–1940. VI.) - Zaveckienė, Žiedūnė (Knygotyra, 1973)
The rare examples of the publishings of the YCL are being kept in the libraries till to-day. Among them we can find not only the central publishings but the publishings of separate districts as well. One can count about 28 of such publishings. 9 of them were issued by the town and district committees of Kaunas, 7 appeared in the district of Panevėžys, 4 – in the district of Šiauliai, 7 in the district of Vilnius (up to 1923). The greatest part of editions (14 from 28) were published in the district of Vilnius (in 1920–1923). The newspapers were published by the committees of secret Komsomol groups, not only in large but in small towns as well, such as Rokiškis, Anykščiai, Biržai.